Taking stock of IFPRI’s experience with country programs - Hazell, Peter B. R.; Place, Frank; Tollens, Eric (International Food Policy Research Institute, 2019)
IFPRI commissioned this study to assess how the country programs (CPs) are performing—which approaches and methods are producing the best outcomes across countries and over time—to identify factors that promote or impede their progress and lessons for making them more impactful in the future. The study has two major components. The first is a survey and analysis of the factors that CP leaders perceived to have most helped them influence host-country policies. We interviewed all current and most past CP leaders, which enabled us to compile evidence from recent CP experiences as well as from the 1980s and 1990s. We focused on the lessons they drew from their past successes that shed light on how to make their other activities successful. We did not undertake similar interviews on failed efforts because it is much harder to elicit such information from CP leaders. Additional insights about unsuccessful activities are, however, captured in the second component of the study, a commissioned external evaluation of the performance of a sample of ongoing country programs. Ideally, the external evaluation would have included CPs in both Africa and Asia, but this was not possible with the available budget. We therefore settled for an evaluation of CPs in Africa south of the Sahara. Doing so had two advantages: (1) the African CPs are more homogenous in terms of their objectives, structure, and internal IFPRI management, making comparisons among them more insightful; and (2) the budget was sufficient to both include all the African CPs in some of the analyses and allow the external evaluator to visit three of them.